A duplicate superior belly of omohyoid muscle: A rare anatomical finding - Benjamin Denoiseux; Nader Ibrahim; Robert Isaac; Elizabeth S. Brennan; Peter A. Brennan (Elsevier, 2023)
The omohyoid muscle is a useful anatomical landmark during neck surgery. The superior belly delineates the inferior limit of a supra-omohyoid neck dissection. We report a rare variant seen during a level I-IV neck dissection surgery with a duplicate superior belly, that initially was confusing in establishing the inferior aspect of level III. We discuss the implications of this finding. A cadaveric and clinical study is in progress.